ANALISIS BIBLIOMETRIK PUBLISH OR PERISH (POP) KEPADA GURU MAN 3 KULONPROGO YOGYAKARTA - Alwazir Abdusshomad; Nawang Kalbuana; Benny Kurnianto; Zulina Kurniawati; Taufik Rohman; Wildan Hidayat (LP2M Universitas Ibrahimy, 2022)
This Community Service Activity was designed to improve teachers’ scientific writing ability as their compulsory professional skills which has been stated in the Minister of Administrative Reform and Bureaucratic Reform Act number 16 of 2009 concerning Teacher Function and Credit Scores. Publishing scientific article becomes one of the required elements and sub-elements of teacher activities to be assessed as credit scores. Hence, the teachers needed the training to write scientific papers as a requirement for their promotion. The training applied a Participatory Learning approach that engaged lecture, practice, and Evaluation. The participants of the training were 30 teachers of MAN 3 Kulonprogo. They were given a lesson to collect articles as references using the bibliometric application Publish or Perish (POP). The evaluation of this Community Service Activity showed that the knowledge value after the training was 2.221 points higher than before training. The paired T-Test sample test worth 0.048 implied that this PKM activity has influenced MAN 3 Kulonprogo Yogyakarta teachers’ skills, especially in improving the teachers’ ability in finding recommended articles.